2023
DOI: 10.3390/foods12061329
|View full text |Cite
|
Sign up to set email alerts
|

Postharvest Biology and Technology of Loquat (Eriobotrya japonica Lindl.)

Abstract: Loquat (Eriobotrya japonica Lindl.) fruit is a rich source of carotenoids, flavonoids, phenolics, sugars, and organic acids. Although it is classified as a non-climacteric fruit, susceptibility to mechanical and physical bruising causes its rapid deterioration by moisture loss and postharvest decay caused by pathogens. Anthracnose, canker, and purple spot are the most prevalent postharvest diseases of loquat fruit. Cold storage has been used for quality management of loquat fruit, but the susceptibility of som… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 137 publications
0
6
0
Order By: Relevance
“…As the fruit matured, the activity of PAL gradually decreased. Previous research has indicated that the decline in PAL activity correlates with reduced lignin content in the cell walls of loquat fruits, contributing to fruit softening [ 40 ]. CAD activity was notably highest at S4, which coincides with the accumulation pattern of neochlorogenic acid.…”
Section: Resultsmentioning
confidence: 99%
“…As the fruit matured, the activity of PAL gradually decreased. Previous research has indicated that the decline in PAL activity correlates with reduced lignin content in the cell walls of loquat fruits, contributing to fruit softening [ 40 ]. CAD activity was notably highest at S4, which coincides with the accumulation pattern of neochlorogenic acid.…”
Section: Resultsmentioning
confidence: 99%
“…Within the flesh, the 'BS' variety notably displayed slightly elevated antioxidant prowess. Notably lauded for its exceptional flavor profile [33,34], we regard the 'BS' variety as a remarkable exemplar that marries both taste and health-enhancing attributes. Nevertheless, the discernible free radical scavenging abilities exhibited by loquats underscore their potential in counteracting alcohol-triggered oxidative stress.…”
Section: Discussionmentioning
confidence: 99%
“…The MO-EC improved the level of the amount of total phenolics during the storage, the content of total phenolics was significantly higher in coated fresh-cut samples than in the control during the whole storage time (Table 3). According to several studies, phenolic compounds play a significant role as non-enzymatic antioxidants and their accumulation may significantly contribute to the scavenging of free radicals, hence lowering the oxidative damage caused to cells in fruits and vegetables by free radicals [4,32,36,37]. Mucilage-based coating enriched with OEO was effective in terms of total phenolics content, MO-EC samples reported values 1.2 times higher than CTR ones at the end of the cold storage period (Table 3).…”
Section: Ascorbic Acid Total Phenolics and Total Carotenoids Contentmentioning
confidence: 92%